Harry Potter and the prisoner of Azkaban [compact disc, unabridged] - Rowling, J. K. (Rowling, J. K. Year ... at Hogwarts, 2000)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.